Korelasi Antara Minat Baca dengan Kemampuan Menulis Teks Eksposisi Siswa Kelas X SMA Negeri 1 Gowa - Yusniar Yusniar; Idawati Idawati; Muhammad Saleh (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research aims to describe students' reading interest, to explain students' ability to write expository texts, and to prove the correlation between reading interest and the ability to write expository texts of class X students at SMA Negeri 1 Gowa. The population of this study was 432 students. The sampling technique is purposive sampling. The sample in this research was class X.7 students, totaling 36 students. The data collection technique uses a reading interest questionnaire and an expository text writing ability test. The validity test uses the product formula, there are 36 or all statements are valid because the calculated r is greater than the r table, data analysis uses descriptive statistical analysis and inferential statistical analysis. The results of the research data description show that students' reading interest can be said to be in the high category with a percentage of 36% and students' ability to write expository texts is in the medium category with a percentage of 42%. From the results of descriptive statistical analysis using the product moment correlation formula, it can be seen that the level of relationship between interest in reading and the ability to write expository texts obtained a calculated r value of 0.782. Meanwhile, the r table with N=36 at the 5% significance level is 0.329. These results show that r count > r table, indicating that there is a positive and significant relationship between interest in reading and the ability to write expository texts in class X SMA Negeri 1 Gowa for the 2024/2025 academic year.